1995
DOI: 10.1139/f95-826
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses and depression of humoral components of the immune system in gilthead sea bream (Sparus aurata) following daily acute stress

Abstract: Changes in the immune system indicators serum hemagglutinating activity, complement levels, antibody titer, and lymphocyte number and in the plasma levels of cortisol and glucose in the gilthead sea bream (Sparus aurata) indicated that stress was induced when fish were chased daily for 8 min with a hand-held net for 16 days. Plasma levels of cortisol and glucose were elevated after 1 day and cortisol remained above prestress levels throughout the experiment. The immune system was altered as indicated by lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
1
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 36 publications
4
45
1
1
Order By: Relevance
“…The increase recorded 4 hours after intraperitoneal injection is in contrast with previous research showing the progressive decrease in haemagglutination activity in gilthead seabream juveniles exposed to repeated acute stress consisting in chasing with a net for 5 minutes over 14 days [7,71]. In the same species, chronic stress induced by crowding caused immunodepression, as suggested by decreases in haemagglutination titre observed after 9 days [72].…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…The increase recorded 4 hours after intraperitoneal injection is in contrast with previous research showing the progressive decrease in haemagglutination activity in gilthead seabream juveniles exposed to repeated acute stress consisting in chasing with a net for 5 minutes over 14 days [7,71]. In the same species, chronic stress induced by crowding caused immunodepression, as suggested by decreases in haemagglutination titre observed after 9 days [72].…”
Section: Discussioncontrasting
confidence: 87%
“…In addition, some components of innate immune system (e.g. lysozyme, haemolytic and haemagglutinating activity) are used as indicators of immunocompetence in fish exposed to stress [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Crowding stress, transportation and other acute stress can dramatically harm complement activity in fish [7,8]. It is desirable to search for substances that have the ability to stimulate Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For the gilthead sea bream, it has been demonstrated that cortisol has mineralocorticoid actions that facilitate adaptation to changes in ambient salinity (Mancera et al 1994, Altimiras et al 1994. In the same fish, crowding and repeated daily acute stress result in immunosuppression (Sunyer et al 1995, Tort et al 1996. In the red gurnard (Chelidonichthys kumu), capture and confinement negatively affect reproduction (Clearwater & Pankhurst 1997).…”
Section: Introductionmentioning
confidence: 99%